TiO2 ceramic varistor modified with tantalum and barium - Gaikwad, A. B.; Navale, SC; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
The non-linear current (I)-voltage (V) characteristics of titanium dioxide doped with small quantities of tantalum and barium (99.9 TiO2 + 0.1 Ta and 99.4 TiO2 + 0.1 Ta + 0.5 Ba, all are in at.%) were investigated. These samples have the non-linear coefficient (alpha) values of (20-30) with high breakdown voltages (E-B similar to 400-700 V mm(-1)). The pentavalent tantalum acts as donor and increases the electronic conductivity. The higher electrical conductivity and decrease in the breakdown field strength with barium addition is attributed to higher density. The acceptor like surface states formed by barium ions segregate to grain boundaries due size misfit to thereby modifying the electrical barrier characteristics of grain boundaries. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Oxides; TiO2; varistor; X-ray diffraction

Varistors based on Ta-doped TiO2 - Navale, S. C.; Murugan, A. Vadivel; Ravi, V. (Ceramics International, 2007)
The nonlinear current (I)-voltage (V) characteristics of titanium dioxide are examined when doped with small quantities (0.05-0.5 at.%) of tantalum pentaoxide. For optimum compositions, the nonlinear coefficients are found to be in the range of 25-30 and the breakdown field strength (EB) is similar to 4000 V/cm. The obtained alpha- and E-B-values are higher than the previously reported values for TiO2 ceramics. The acceptor like surface states at the grain boundary adsorb oxygen during sintering and cooling, leading to formation of grain boundary barrier. The grain boundary barrier height (OB) is calculated using Schottky equation. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Oxides; Schottky barrier; TiO2; varistor